Serum insulin‐like growth factor 1 and facial ageing: high levels associate with reduced skin wrinkling in a cross‐sectional study. (31st January 2013) - Noordam, R.; Gunn, D.A.; Tomlin, C.C.; Maier, A.B.; Griffiths, T.; Catt, S.D.; Ogden, S.; Slagboom, P.E.; Westendorp, R.G.J.; Griffiths, C.E.M.; van Heemst, D.; de Craen, A.J.M.; et al.
Summary Background Insulin‐like growth factor (IGF)‐1 is a growth factor that can influence fibroblast functioning, with effects including the inhibition of collagenases and the induction of collagen expression. Objectives To assess whether serum IGF‐1, IGF‐binding protein (IGFBP)3 and the ratio between IGF‐1 and IGFBP3, as a measure of IGF‐1 bioavailability, are associated with facial ageing and skin wrinkling. Methods From a random sample comprising 617 subjects from the Leiden Longevity Study, perceived age and skin wrinkling were assessed from facial photographs, and IGF‐1 and IGFBP3 were measured in serum. The associations were assessed using linear regression models, adjusted for chronological age, sex, body mass index, smoking and sun exposure. Results Across tertiles of the ratio of IGF‐1 to IGFBP3, and after adjusting for all potential confounding factors, the mean perceived age decreased from 60·6 years in the lowest tertile to 59·5 years in the highest (Ptrend = 0·045). Similarly, the mean skin wrinkling grade decreased from 4·8 in the lowest tertile to 4·5 in the highest (Ptrend = 0·011). Adding skin wrinkling as a covariate in the analysis between IGF‐1 and perceived age diminished this association. Conclusions This study demonstrates that a higher ratio of IGF‐1 to IGFBP3 associates with a lower perceived age, via its association with reduced skin wrinkling. Whether high IGF‐1 levels actually delay the accumulation of skin wrinkling now needs investigating.